An alternative non-vacuum and low cost ESAVD method for the deposition of Cu(In,Ga)Se2 absorber layers - Wang, Mingqing; Hou, Xianghui; Liu, Junpeng; Choy, KwangLeong; Gibson, Paul; Salem, Elhamali; Koutsogeorgis, Demosthenes; Cranton, Wayne (Wiley, 2015)
In this article, an environmentally friendly and non vacuum electrostatic spray assisted vapour deposition (ESAVD) process has been developed as an alternative and low cost method to deposit CIGS absorber layers. ESAVD is a non-vacuum chemical vapour deposition based process whereby a mixture of chemical precursors is atomized to form aerosol. The aerosol is charged and directed towards a heated substrate where it would undergo decomposition and chemical reaction to deposit a stable solid film onto the substrate. A sol containing copper, indium and gallium salts, as well as thiourea was formulated into a homogene-ous chemical precursor mixture for the deposition of CIGS films. After selenization, both XRD and Raman results show the presence of the characteristic peaks of CIGSSe in the fabricated thin films. From SEM images and XRF results, it can be seen that the deposited absorbers are promising for good performance solar cells. The fabricated solar cell with a typical structure of glass/Mo/CIGSSe/CdS/i-ZnO/ITO shows efficiency of 2.82% under 100mW/cm2 AM1.5 illumination.